Busines development opportunities through pursuit of joint-venture initiatives in construction - Preece, Christopher Nigel; Hasan, Sharina Farihah (2010)
A joint venture involves two or more businesses pooling their resources and expertise to achieve a particular goal, eg the construction of a large building. The risks and rewards are also shared. Businesses of any size can use joint ventures to strengthen long termbusiness/marketing relationships, or to collaborate on short-term projects, but entering into a joint venture is a major decision. The benefits of a joint ventuer include: the costs nad risks of the project are spread, improved access to financial resources, economies of scale and advantage od size, access to new technologies and customers, pre-empting competitionand creation of stronger competitive units.